Effectiveness of a cognitive behavioural therapy-based anxiety prevention programme for children: a preliminary quasi-experimental study in Japan. Issue 1 (December 2016) - Urao, Yuko; Yoshinaga, Naoki; Asano, Kenichi; Ishikawa, Ryotaro; Tano, Aya; Sato, Yasunori; Shimizu, Eiji
Abstract Background As children's mental health problems become more complex, more effective prevention is needed. Though various anxiety and depression prevention programmes based on cognitive behavioural therapy (CBT) were developed and evaluated in Europe, North America, and Australia recently, there are no programmes in Japan. This study developed a CBT programme for Japanese children and tried to verify its effectiveness in reducing anxiety. Methods A CBT-based anxiety prevention programme, 'Journey of the Brave', was developed to prevent anxiety disorders for Japanese children. Children from 4th through 6th grades (9–12 years old) in Japanese elementary schools and their parents (13 sample pairs) were the intervention group. For comparison purposes, 16 pairs were the control group. Ten weekly programme sessions and two follow-ups were conducted. Children's anxiety levels in both groups were evaluated by child and parent self-reports using the spence children anxiety scale (SCAS) three times: pre-programme (baseline), post-programme, and 3 months following the end of the programme. Results At 3-month follow-up, no significant difference was shown between the intervention and control groups on children's SCAS scores in changes from baseline by using mixed-effects model for repeated measures analysis (SCAS-C: −8.92 (95 % CI = −14.12 to −3.72) and −3.17 (95 % CI = −8.02 to 1.66) respectively; the between group difference was 5.747 (95 % CI = −1.355 to −12.85, p = 0.062). On the other hand, significant reduction was shown in the intervention group on parents' SCAS (SCAS-P) scores in change from baseline −9.554 (95 % CI = −12.91 to −6.19) and 0.154 (95 % CI = −2.88 to 3.19) respectively; the between group difference was 9.709 (95 % CI = 5.179 to 14.23, p = 0.0001). Conclusion These preliminary results suggest this anxiety prevention programme for Japanese children was partially effective from parents' evaluations. However, it is important to note that this study was conducted on a small sample with unbalanced groups at pre-intervention with no randomization. The positive results may require discounting due to the research limitations. A larger-scale study of the programme in elementary school classes to verify its effectiveness with a more rigorous research design is necessary. Trial registration : UMIN-CTR UMIN000009021